Perilaku Nonlinier Buckling pada Struktur Cangkang Bola - Sumirin, Sumirin; nuroji, nuroji (Department of Civil Engineering, Diponegoro University, 2014)
This paper presents the results of a numerical study using the finite element method in geometrical nonlinear on camped shallow spherical shells under uniform pressure. The shell structure was modelled by finite axisymmetric thin shell elements and quadrilateral elements. The geometrical nonlininear problem was solved by a scheme of incremental iterative procedures applying Newton-Raphson method in combination with arch length methods. The results of finite element analysis compared with the experimental results of previous reseacher.